2007
DOI: 10.1136/gut.2006.100016
|View full text |Cite
|
Sign up to set email alerts
|

Visceral pain perception is determined by the duration of colitis and associated neuropeptide expression in the mouse

Abstract: Background: Even though inflammation is a traditional tool for the induction of hyperalgesia in many tissues, recent observations suggest that not all inflammatory processes produce this change. Tolerance to colorectal distension (CRD) is reduced in patients with acute ulcerative colitis but is increased in patients with chronic inflammatory bowel disease. This suggests that the nature of the inflammatory infiltrate influences visceral perception. Aim: To test this hypothesis by assessing responses to CRD in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
77
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 31 publications
6
77
0
1
Order By: Relevance
“…Indeed patients with Crohn's disease and Ulcerative Colitis experience hyposensitivity to rectal balloon pressure, which has previously been attributed to alterations in the central nervous system processing and descending inhibitory nervous pathways (Bernstein et al, 1996;Chang et al, 2000). Our studies indicate immune derived β-endorphin may also provide inhibitory influences in IBD , as has been described in mouse models of colonic inflammation, however this is yet to be investigated in humans (Valdez-Morales et al, 2013;Verma-Gandhu et al, 2007).…”
supporting
confidence: 57%
“…Indeed patients with Crohn's disease and Ulcerative Colitis experience hyposensitivity to rectal balloon pressure, which has previously been attributed to alterations in the central nervous system processing and descending inhibitory nervous pathways (Bernstein et al, 1996;Chang et al, 2000). Our studies indicate immune derived β-endorphin may also provide inhibitory influences in IBD , as has been described in mouse models of colonic inflammation, however this is yet to be investigated in humans (Valdez-Morales et al, 2013;Verma-Gandhu et al, 2007).…”
supporting
confidence: 57%
“…Another recent study, however, has shown that during acute DSS-induced colitis, male mice did develop increased responses toward noxious colonic distension (31). Moreover, in chronic DSS-induced colitis, induced by repetitive cycles of DSS administration to male mice, increased visceral perception did not occur (31).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study, however, has shown that during acute DSS-induced colitis, male mice did develop increased responses toward noxious colonic distension (31). Moreover, in chronic DSS-induced colitis, induced by repetitive cycles of DSS administration to male mice, increased visceral perception did not occur (31). Despite the conflicting results whether visceral hypersensitivity occurs during colitis, our present data clearly demonstrated that after resolution of DSS-induced colitis the visceral pain response to intracolonic capsaicin is increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They provide the organism with mechanisms to cope with environmental stress, such as mechanical stress, tissue injury, pathogen invasion, inflammation, tumor growth, and others (Schäfer, 2010). Opioid peptides and their receptors mediate a wide variety of effects including pain (Schäfer, 2010), gastrointestinal motility (Verma-Gandhu et al, 2007), respiration (Krajnik et al, 2009;Mahler et al, 2009), and cardiac function (Kasper et al, 1992;Barry and Zuo, 2005;Mousa et al, 2010). Pharmacologic and molecular studies have identified three opioid receptors: l (M), j-(K), and d (D) opioid receptors (ORs) (Schä-fer, 2010).…”
mentioning
confidence: 98%